The McKenzie Method versus guideline-based advice in the treatment of sciatica: 24-month outcomes of a randomised clinical trial - Kilpikoski, Sinikka; Häkkinen, Arja H; Repo, Jussi P; Kyrölä, Kati; Multanen, Juhani; Kankaanpää, Markku; Vainionpää, Aki; Takala, Esa-Pekka; Kautiainen, Hannu; Ylinen, Jari (Clinical rehabilitation, 2024)
To compare the effectiveness of a McKenzie Method intervention in patients with sciatica with guideline-based patient education.OBJECTIVETo compare the effectiveness of a McKenzie Method intervention in patients with sciatica with guideline-based patient education.Multi-centre, assessor-blinded, parallel-group, randomised trial.DESIGNMulti-centre, assessor-blinded, parallel-group, randomised trial.Two tertiary hospitals providing operative spinal care.SETTINGTwo tertiary hospitals providing operative spinal care.Sciatica patients with magnetic resonance imaging-confirmed lumbar disc herniation compressing a nerve root.SUBJECTSSciatica patients with magnetic resonance imaging-confirmed lumbar disc herniation compressing a nerve root.The McKenzie group received specific back exercises for seven visits combined with an educational book, and the Control group received a single session of self-management guidance according to usual practices.INTERVENTIONSThe McKenzie group received specific back exercises for seven visits combined with an educational book, and the Control group received a single session of self-management guidance according to usual practices.The primary outcome was the number of surgical operations. Secondary outcomes were pain measured using the Visual Analogue Scale, disability using the Oswestry Disability Index and health-related quality of life using a RAND-36 questionnaire at baseline and 24-month follow-up.MAIN MEASURESThe primary outcome was the number of surgical operations. Secondary outcomes were pain measured using the Visual Analogue Scale, disability using the Oswestry Disability Index and health-related quality of life using a RAND-36 questionnaire at baseline and 24-month follow-up.Altogether 66 patients, mean age of 43 years, of which 50% were females with long-lasting sciatica, mean 16 weeks, were randomised to two groups. Nineteen patients (29%) had surgery. There was no significant difference in surgery rates between the groups. Back and leg pain decreased, and disability improved in both groups. Health-related quality of life improved in six dimensions out of eight in both groups. There were no significant between-group changes in the patient-reported outcomes at the follow-up.RESULTSAltogether 66 patients, mean age of 43 years, of which 50% were females with long-lasting sciatica, mean 16 weeks, were randomised to two groups. Nineteen patients (29%) had surgery. There was no significant difference in surgery rates between the groups. Back and leg pain decreased, and disability improved in both groups. Health-related quality of life improved in six dimensions out of eight in both groups. There were no significant between-group changes in the patient-reported outcomes at the follow-up.Multiple sessions of McKenzie-based back exercises with a McKenzie-specific patient's educational book produced effects equal to guideline-based advice at long-term follow-up. However, the power of these results is diminished due to the small patient population and confounding factors.CONCLUSIONSMultiple sessions of McKenzie-based back exercises with a McKenzie-specific patient's educational book produced effects equal to guideline-based advice at long-term follow-up. However, the power of these results is diminished due to the small patient population and confounding factors.